A Study of Dynamic Equivalence Method for Multiple Wind Farms in Urban Power Grids - Zhu, Lin; Huang, Shiyu; Wu, Zhigang; Hu, Yonghao; Liao, Mengjun; Xu, Min (Frontiers in Energy Research, 2022)
As the number of wind farms (WFs) in urban power grids gradually increases, their dynamic equivalence is needed for stability analysis. This paper proposes a dynamic equivalence method for distributed multiple wind farms in an urban power grid. The key idea is to characterize wind farms dynamics and then use them for coherence by considering the differences between doubly-fed induction generators (DFIG) and permanent magnet direct-drive synchronous generators (PMSG). The mathematical-physical models and operational control characteristics are firstly analyzed to find the essential attributes representing the dynamic characteristics. Then we introduce the similarity based on the dynamic timing warping (DTW) distances, which help construct the clustering index for coherency wind farms. Meanwhile, comprehensive constraints, which ensure the consistency of the urban power grid topology, are adequately considered. Finally, the parameters of coherent wind farms are aggregated based on the clustering groups. The proposed method is validated in an urban grid by the time-domain simulation.